Gambaran umum status anemia dan prestasi belajar anak usia sekolah dasar di SD Negeri 4 Abiansemal - Ida Ayu Mas Suryani; Bagus Komang Satriyasa (E-Jurnal Medika Udayana, 2018)
Anemia is a condition of concentration of red blood cells that carries oxygen in the blood (Hb) is not sufficient for the physiological body needs. Anemia resulting decreases immune tend to get infections, impaired school performance because of having difficulty concentrating. The purpose of this study to describe the incidence of anemia and learning achievement of children in SD Negeri 4 Abiansemal, Badung, Bali conducted from August to November 2015. This study used cross sectional design include 44 respondents. Respondents filled out a questionnaire symptoms of anemia, the data retrieved grades, and hemoglobin levels were measured using HemoSmart Gold. Symptoms of anemia, the data grades, and hemoglobin levels were analyzed using a Chi Square test and Simple Linear Regression test. Results of study there are differences in learning achievement of children who are anemic and not anemic. The prevalence of anemia in SD Negeri 4 Abiansemal is 34.1%. Most of the subjects were female (52.3%), mean age 10 years (45.5%), father education is high school education (79.5%), the mother education is high school education (72.7%), father’s occupation not labor/farmers/traders (59.1%), working mothers (77.3%), suspected symptoms of worm infection (2.3%), underweight (63.6%), good learning achievement (54.5%). Keywords: anemia, elementary school students, learning achievement